LEGAL TRAINING OF STAFF IN THE FIELD OF INFORMATION SECURITY - Sleptsov, V. I.; Karpukov, L. M (Radio Electronics, Computer Science, Control, 2024)
Some questions of legal preparation of specialists are examined on directions, to included in the field of knowledges «Informative safety», taking into account the specific of their future professional activity, educational tasks, legislation of Ukraine and experience department of priv the Zaporozhia national technical university.